An assessment of the wild cyclopia subternata (vleitee) resource - Van der Walt, Wouter (Rhodes University, Faculty of Science, Department of Geography)
Cyclopia spp. is used for the production of Honeybush tea, an herbal tea which is used in many cases as a substitute for rooibos tea. The wild harvesting of this fynbos plant still brings in up to 85% of the annual crop and as such needs to be carefully monitored in order to avoid over harvesting and the destruction of biodiversity within the Eastern and Western Cape mountain regions of Southern Africa. Due to the concerns of overharvesting and unsuitable use of the wild resource issues of supply security have been raised. There is a lack of formal knowledge relating to the plant, its harvesting, the industry and its economic potential. This study aimed to amend this scarcity by contributing to the knowledge of C. subternata as a wild harvested plant, the physical environment favoured by C. subternata, sustainable use through harvesting of the wild plant and harvesting methods specific to this honeybush species. The research concludes by presenting a guideline for best harvest practices of the wild C. subternata plant.
Keywords: Legumes -- South Africa; Fynbos -- South Africa; Fynbos ecology -- South Africa; Fynbos -- Harvesting -- South Africa; Biodiversity conservation -- South Africa; Traditional ecological knowledge -- South Africa; Wild Cyclopia Subternata (Vleitee); Honeybush tea industry